Elastic modulus of steel fibre reinforced concrete and steel fibre self-compacting concrete [electronic resource] - Owi, Siew Feen, 1990-, author; Roslli Noor Mohamed, Dr., supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2014